2013
DOI: 10.1097/inf.0b013e31827c9726
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Meningitis in a Previously Healthy 13-year-old Child

Abstract: Keywords eosinophilic meningitis; Angiostrongylus cantonensis; rat lung wormA previously healthy 13-year-old male developed acute onset of a bi-temporal headache. The headache persisted, and two weeks later, he was diagnosed with sinusitis and was given amoxicillin. On illness day 17, he experienced worsening headache, slurred speech, transient left facial droop, right hand numbness, and dizziness. At a local emergency department (ED), magnetic resonance imaging (MRI) of the brain showed no significant abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Trevor J. Slom et al reported that among 9 hospitalized patients with suspected EM caused by A. cantonensis, only 5 had CSF eosinophilia in the initial lumbar puncture [26], and 8 of the 9 patients finally exhibited CSF eosinophilia after hospitalization, although detailed changes in the patient blood eosinophil counts were not clearly reported. Furthermore, there has been a case report about a pediatric patient with A. cantonensis-induced EM within the USA [27]. His first CSF sample showed a WBC count of 763/mm 3 with 5% eosinophils, but later his CSF showed high eosinophilia, reaching 21% of the CSF WBCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trevor J. Slom et al reported that among 9 hospitalized patients with suspected EM caused by A. cantonensis, only 5 had CSF eosinophilia in the initial lumbar puncture [26], and 8 of the 9 patients finally exhibited CSF eosinophilia after hospitalization, although detailed changes in the patient blood eosinophil counts were not clearly reported. Furthermore, there has been a case report about a pediatric patient with A. cantonensis-induced EM within the USA [27]. His first CSF sample showed a WBC count of 763/mm 3 with 5% eosinophils, but later his CSF showed high eosinophilia, reaching 21% of the CSF WBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there has been a case report about a pediatric patient with A . cantonensis -induced EM within the USA [ 27 ]. His first CSF sample showed a WBC count of 763/mm 3 with 5% eosinophils, but later his CSF showed high eosinophilia, reaching 21% of the CSF WBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first publication of the biological method in 2010 [ 17 ], it has been mainly used for the identification of the vector, especially in Hawaii, USA and Brazil [ 25 , 37 , 38 ]. Some publications reported the use of real time PCR for the diagnosis of human angiostrongyliasis, and not always successfully, in Hawaii and in Brazil [ 39 , 40 ]. We present here the most important positive case series, and demonstrate the great interest of this tool for the confirmatory diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and epidemiological details have been presented elsewhere for six of the patients. [25][26][27][28][29] Five patients had knowingly ingested raw snails: four as part of exotic cuisine, one as a dare. Two patients were part of an outbreak in Jamaica where a Caesar salad was implicated as the source of infection.…”
Section: Discussionmentioning
confidence: 99%